IMPLEMENTASI AKUNTANSI SEBAGAI STRATEGI BISNIS UMKM - Halpiah, Halpiah; Putra, Hery Astika (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
This research is motivated by various problems faced by MSMEs in bread, tofu, sasak culinary, cowhide crackers, and welding in the Mataram City Region. Especially the problem of limited access to capital, the absence of preparation of financial statements so that the business that is run is stagnant and does not develop even though it has been occupied for 10-20 years. Therefore, researchers are interested in carrying out research with the theme "Accounting as a Business Strategy" using a qualitative method of phenomenological approach with the results of research that accounting forces MSME actors to improve their management systems, make financial reports that can be used as a basis for making business decisions, and can be used by other parties. banks to analyze the feasibility of granting credit to MSME actors so that access to capital injections is wide open